21 Development of a digital self-care management application for children with Uveitis: Uveitis Patient Passport. (30th November 2020) - Kretova, Elizaveta; Rahman, Asrath; Bassi, Daiana; Fu, Yun; Mohamedally, Dean; Molyneux, Gemma; Roberts, Graham; Sebire, Neil J; Rahi, Jugnoo; Solebo, Ameenat Lola
Abstract : Childhood uveitis is a chronic, sight threatening inflammatory eye condition. There are a complex range of different disorders within the collective term of uveitis. Children can have associated systemic inflammatory disorders, and are treated with systemic chemotherapies which need frequent monitoring. For many, the uveitis continues to be active in adulthood. Care for children with uveitis is multi-centre and multi-disciplinary. A child's primary care team may be located in a geographically distant location, acting as an obstacle to informing teams at local hospitals, particularly when children present acutely with problems associated with their eye disease, systemic disease or treatment. It can also be a challenge to educate young people about their disease, which is vital to support transition. A paper based 'Uveitis Passport' existed to support self-care for adults with uveitis. This paper based personal record was well received, but was not designed for use in children and young people. We have undertaken a project to create a digital mobile app specifically aimed at children to support them, and their families, to take control of their condition. In collaboration with UCL computer science, through the industry exchange network, researchers at GOSH and UCL GOS Institute of Child Health developed a mobile app to support Uveitis self-management. The adult 'passport' content was modified with the support of children and families. The application front-end was developed in Ionic. The back-end consists of an internal SQLite Database that provides the mobile app with direct read and write access to the data, stored locally in a single file. The mobile app developed allows patients to record important information about their condition. The app will support patient self-management, and empower patients when accessing services outside of their normal care team. This app could be modified to support a variety of childhood chronic conditions.